Dilemmas and Opportunities for Rural School Sports in the Context of Sports Immersion Action Plans - Wei, Hongmei (International Journal of Social Sciences and Public Administration, 2024)
In the process of rapid economic development, our country has formed a serious urban-rural dual economic structure, resulting in rural areas in the economy, education, infrastructure, etc.  In this paper, the author summarizes the predicament of rural school sports development and analyzes the opportunities brought by the implementation of the national sports infiltration action plan. The research shows that there are some problems in school physical education in rural areas of our country, such as weak sports consciousness, weak sports teachers, lack of sports facilities, lack of sports curriculum features and so on The implementation of the action plan on sports infiltration is conducive to consolidating the status of sports in school education, improving the level of teachers, alleviating the shortage of sports equipment, and expanding the resources of sports courses and after-school activities.